GRAMMAR FOCUS ANALYSIS IN ENGLISH TEXTBOOK FOR SENIOR HIGH SCHOOL ON TENTH GRADE STUDENT’S: A SYNTAX PERSPECTIVE - Ferdias Prihatnasari (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2020)
Grammar is one apsect in studying English. It is a must for the learners to master grammar. But there are a lot of aspects in grammar that should be mastered not only by the students but also the teachers. The apsects in grammar sometimes confuse not only the srudents but also the teachers. Some ways are used as the teaching media to support the English teaching learning process. English textbook is one of them. Grammar is one of the aspect that is discussed in English textbook. There are a lot of aspects of grammar that is dicussed. Grammar relates to syntax. They are connected becase there are many aspects in Syntax. This research analyzes about grammar focus in textbooks used by senior high school, English Zone and English book. The reason why this topic is chosen since the curiosity demands to know whether the textbooks used in school is fulfilled or not in terms of grammar. The problems discussed are how grammar focus in English Zone and English book are revealed. In order to find out the answer, grammar focus in English textbook for senior high school on tenth grade student is used. The participants of this research were the grade tenth students in senior high school. To do the research they were asked to Based on the analyses, it is found that the aspects of grammar focus are revealed in every word.